The impact of health information echo chambers on older adults avoidance behavior: the mediating role of information fatigue and the moderating role of trait mindfulness - Zhong, Fuxiu; Gu, Chenyu (Frontiers in Psychology, 2024)
Background: In the digital media era, the prevalence of algorithm-driven content push has intensified the health information echo chambers phenomenon, characterized by excessive homogenization and overload of information. This phenomenon may negatively impact the elderly, a "digitally vulnerable" group, by limiting their access to diverse health information and potentially inducing health information avoidance behaviors. However, the psychological mechanisms within this impact process remain unclear, and this study aims to explore them. Additionally, current study introduces trait mindfulness as a potential intervention tool in reducing health information avoidance behavior among the elderly.Methods: This study constructs an impact model based on the Stress-Coping Theory and the Stress-Strain-Outcome (SSO) framework. It identifies health information similarity, relevance, and overload as characteristics of the echo chamber, constituting the Stress part; information fatigue as the Strain; and health information avoidance as the Outcome, with trait mindfulness serving as a moderating factor between Strain and Outcome. A cross-sectional survey of 236 elderly individuals aged 60 and above was conducted, and the collected data were analyzed using SmartPLS and SPSS.The study found that health information similarity and overload significantly increased health information fatigue among the elderly, thereby promoting avoidance behavior, but no significant correlation was found between relevance and fatigue. While there was no significant correlation between trait mindfulness and health information fatigue, it effectively moderated the avoidance behavior induced by fatigue.Current study reveals the impact of the health information echo chamber phenomenon on health information avoidance behavior among the elderly and the moderating role of trait mindfulness. It emphasizes the importance of breaking the health information echo chamber and promoting diverse information dissemination to improve the health information behavior of the elderly. Furthermore, the moderating role of trait mindfulness demonstrates positive intervention potential, providing the elderly with a psychological adjustment mechanism to accept and process health information with a more open attitude, thereby reducing unproductive avoidance behavior.